Persistent comorbid symptoms of depression and anxiety predict mortality in heart disease - Doering, L.; Moser, D.; Riegel, B.; McKinley, S.; Davidson, Patricia; Baker, H.; Meischke, H.; Dracup, K. (Elsevier, 2010)
Background. Incident anxiety and depression are associated separately with cardiac events and mortality in patients after acute coronary syndromes, but the influence of persistent comorbid depression and anxiety on mortality remains unknown. The purpose of this study was to determine the prevalence of comorbid persistent depressive and anxious symptoms in individuals with ischemic heart disease and to evaluate effects on mortality. Methods. Prospective, longitudinal cohort design in the context of a randomized trial to decrease patient delay in seeking treatment for ischemic heart symptoms (PROMOTION trial) was used, with twelve-month follow-up of 2325 individuals with stable ischemic heart disease. Participants were assessed on enrollment and at 3 months using the Multiple Adjective Affect Checklist and the Brief Symptom Inventory for depressive and anxious symptoms, respectively. Results. At 3 months, 608 individuals (61.7%) reported persistent symptoms of depression, anxiety, or both. Three hundred seventy-nine (42.5%) and 1056 (45.4%) had persistent anxious and depressive symptoms, respectively. Those with persistent, comorbid symptoms had higher mortality compared to others (p = .029). The combined presence of anxious and depressive symptoms contributed significantly to mortality when compared to symptom-free participants (OR 2.35, 95% CI 1.23–4.47, p = .010). The presence of persistent depressive symptoms only and persistent anxious symptoms only were not associated with death, when other demographic and clinical variables were considered. Conclusions. Persistent symptoms of anxiety and depression increased substantially the risk of death in patients with ischemic heart disease. Future research into shared and unique pathways and treatments is needed.